Management of PCOS Through Ayurvedic Approaches: The Role of Panchakarma (International Journal of Ayurveda and Pharma Research, 2024)
Among women of reproductive age, PCOS is a widespread metabolic and reproductive disorder that can disrupt menstrual cycles, fertility, hormonal equilibrium, and physical appearance. Manifestations may include acne, facial hair growth, fatigue, susceptibility to UTIs, and hair loss. In Ayurvedic texts, Acharya Charak classified it as Vinshati Yonivyapada, Acharya Sushruta referred to it as Nashtartava, and Acharya Kashyapa described it as Pushpaghni Jataharini, all with symptoms resembling those of PCOS. In contemporary medicine, hormonal therapy and other medications are often prescribed for PCOS, despite potential long-term adverse effects. Hence, Panchakarma could offer a preferable treatment approach, utilizing Shodhan Chikitsa (purification therapy) alongside lifestyle adjustments for managing PCOS more effectively. At Sanjeevani Chikitsalya in Jodhpur, a 21-year-old female diagnosed with PCOS, presenting symptoms of irregular menstrual cycles, rashes and itching in the hip region, generalized weakness, and UTI infections for the past two years, underwent successful treatment. The approach involved Shodhan Chikitsa, specifically Virechana Karma.